Solution‐Processed Multifunctional Thin‐Film Encapsulation of Perovskite Thin Films and Devices - Abdul Khaleed; Hongbo Mo; Ali Asghar Syed; Atta Ur Rehman; Yin Li; Jingbo Wang; Yixuan Wang; Tao Zhu; Yanting Shen; Gang Li; Kaimin Shih; Aleksandra B. Djurišić (Advanced Energy & Sustainability Research)
Herein, the effect of multicomponent composite encapsulation on the stability of perovskite thin films and perovskite solar cells, as well as lead leakage upon water immersion, is investigated. The encapsulation is simple and low cost since it is entirely deposited by solution processed techniques in the ambient atmosphere. It consists of a spray‐coated composite layer sandwiched between two spin‐coated layers. The composite layer contains hygroscopic nanomaterials, oxygen scavengers, and lead adsorbing nanomaterials, which enables reduced lead leakage and improved stability of encapsulated perovskite during storage in ambient, immersion in water, as well as illumination in dry air. The encapsulation layers show high transmittance and did not have a significant effect on the short‐circuit current density and open‐circuit voltage despite the deposition of encapsulation in ambient air. The encapsulated devices retain 80% of their initial performance after 4 h of immersion in water.